Acceptability and applicability of using virtual reality for training mass casualty incidents- a mixed method study - Sara Heldring; Maria Jirwe; Jonas Wihlborg; Veronica Lindström (BMC Medical Education)
Abstract Background Because health professionals can end up being first responders to a mass casualty incident, they must train to improve preparedness and increase the preconditions of victim outcomes. Training and learning on how to handle a mass casualty incident is traditionally based on reading, lectures, training through computer-based scenarios, or sometimes through live simulations. Professionals should practice in realistic environments to narrow the theory–practice gap, and the possibility of repeating the training is important for learning. Virtual reality is a promising tool for realistic and repeatable simulation training, but it needs further evaluation. This study aimed to describe the acceptability and applicability of using VR for training in mass casualty incidents. Methods A mixed-methods evaluation design was used, where the qualitative and quantitative findings were embedded into the discussion with a realist inquiry approach. A virtual reality simulation with mass casualty incident scenarios, named GoSaveThem ( www.crash.nu ), was used, and the participants were directed to perform triage. After the simulation, the participants filled in a questionnaire with open-ended questions and ratings on technical aspects, learning experiences, and improvement of preparedness. Eleven of the participants underwent interviews. The qualitative data was analyzed either summarily or with a conventional content analysis. Data were extracted from computer recordings of how long it took for each participant to triage the first 10 victims and to what extent the triage for the first 10 victims was correct. Descriptive statistical analyses were done, and a comparison was made to see if there were any differences between age, sex, educational background, and previous experiences that affected the outcome of triaging. Results Training with virtual reality enables repeatable and realistic simulation training of mass casualty incidents. The participants expressed motivation to repeat the training and experience expanded virtual reality scenarios. This study shows that the acceptability and applicability of using VR for training MCIs were high overall in all examined dimensions for most users, with some exceptions.